The need to ensure the emotional and intellectual development of future music teachers in modern education (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the essential points of harmonization of intellectual and emotional components training the future teachers of music for their professional activity: it also correlates the intellectual models and defines the possible ways of pedagogical technologies usage, considering various emotional factors.
Keywords: intelligence; emotions; computer technologies in music